Consumption intention toward ethnic food: determinants of Dayak food choice by Malaysians - Hiram, Ting; Tan, Sharon; Nastassia, John Alexandra (Elsevier B.V., 2017)
The awareness and trying of ethnic cuisine have increased due to the developing exchange of trade, movement of ethnicities across the globe, and tourist traveling opportunities. More people consume ethnic food for the appreciation of the culture and taste. Although the Dayaks are the largest indigenous group in Malaysia, little is done to date to explicate why Malaysians consume Dayak food. The present study aims to investigate the Dayak food choice of non-Dayak Malaysians and to assess its effect on consumption intention. Self-administered questionnaire-based survey was used, and 195 respondents were sampled purposively in Malaysia. The results show that only health consideration and sensory appeal have a positive effect on the intention to consume Dayak food. It implies that most Malaysians consume only selected Dayak dishes occasionally. Practical implications of the study are provided.